Validation of a novel technique with radioactive implanted ions for recession rate estimate of aerospace material. (2nd June 2021) - Rapagnani, D; De Cesare, M; Buompane, R; Del Vecchio, A; Di Leva, A; D'Onofrio, A; Porzio, G; Gialanella, L
Abstract: Durability tests of thermal protection system (TPS) materials for space vehicles is of paramount importance in developing TPS materials. The limits of the presently used techniques and the need for higher accuracy and precision demand new reliable and more sensitive measurement methods. In this paper we present the validation of a new on-line and non intrusive technique to estimate the TPS material recession rate which exploits the surface layer implantation of radioactive 7 Be ions and the measurement of its characteristic γ -rays during the recession test.